Optimizing Blockchain Waqf as An Instrument for The Sustainability of Pesantren Education - Akhmad Affandi Mahfudz; Syahrul Ihsan; Syamsuri Syamsuri; Mohd Sollehudin Shuib (Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2025)
The emergence of the need for sustainable education, makes waqf a potential solution to support pesantren education by utilizing technology. The role of blockchain as a cutting-edge technology and the development of waqf-based Pesantrens in Indonesia make this study crucial. This article discusses the optimization of waqf as an instrument to support the sustainability of pesantren education by utilizing blockchain technology. This study uses a qualitative methodology to explore the integration of blockchain technology in the pesantren waqf system comprehensively. This study uses a literature study approach from secondary data. The results of the study indicate that the implementation of blockchain in pesantren waqf can increase transparency through irreversible transaction recording, accelerate the distribution of benefits and maintain accountability with smart contracts, even its traceable nature can increase public or waqif trust in waqf management in Pesantrens. In addition, the purpose of this study is to provide an appropriate waqf optimization strategy by utilizing blockchain technology to produce sustainable education. The conclusion of this study emphasizes the use of blockchain which has great potential in optimizing waqf management for the sustainability of pesantren education, but its implementation requires the right adaptation strategy and readiness of waqf managers. The contribution of the study is in the form of literacy of blockchain-based waqf digitalization in Pesantrens and opens opportunities for further research related to practical and policy aspects.